Value of pathohistology in diagnostics of chronic-inflammatory bowel diseases Stellenwert der Pathohistologie bei der Diagnostik von chronisch- entzndlichen Darmerkrankungen - Vieth, Michael; Langner, C.; Neumann, Helmut (Endoskopie heute, 2011)
The most 3 common forms of colitis are infectious colitis, ulcerative colitis and Crohns disease. The histological distinction is possible but can be difficult. Important are the clinical data. Even more difficult is the distinction of sporadic adenoma and colitis-associated neoplasia. Such cases are not frequent but distinction is important as further clinical procedures needs to be planned. Molecular markers can help for differential diagnosis. Taken down to a single case such markers may be not useful at all. Goldstandard is still the experienced pathologist with diagnosis on routine H&E sections. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2025-03-05
Keywords: adenoma; colitis; Crohns disease; histology; infection; ulcerative colitis